A PROPOSITO DE "LA BUONA SCUOLA” - Selvini, Attilio; Monti, Carlo (GEOmedia, 2015)
The article relates some grammatical errors and terminology that were found in the second written test prepared by the Ministry of Education to perform the profession of surveyors. The opinion that the International Federation of Surveyors will make on the reliability and competence of the Ministry of Education and, not only on those who composed the theme but also on those who have graduated, surely innocent, but without having faced a written test worth to be called such, it may not be the best.